2016
DOI: 10.1016/j.neuroscience.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-androgenic steroids decrease dendritic spine density in the nucleus accumbens of male rats

Abstract: Recent studies have demonstrated that anabolic-androgenic steroids (AAS) modify cognitive processes such as decision making and behavioral flexibility. However, the neural mechanisms underlying these AAS-induced cognitive changes remain poorly understood. The mesocorticolimbic dopamine (DA) system, particularly the nucleus accumbens (Acb), is important for reward, motivated behavior, and higher cognitive processes such as decision making. Therefore, AAS-induced plasticity in the DA system is a potential struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
3
20
0
1
Order By: Relevance
“…These effects seem to be region-specific within the striatum, as estrogenic effects on spine density and excitatory synaptic properties observed in the NAc were not seen in the caudate-putamen ( 197 , 198 ). The effects of gonadal hormones on NAc physiology is not limited to females, as long-term treatment with androgens in males also modulates NAc dendritic spine density ( 200 ).…”
Section: Reward Systemsmentioning
confidence: 99%
“…These effects seem to be region-specific within the striatum, as estrogenic effects on spine density and excitatory synaptic properties observed in the NAc were not seen in the caudate-putamen ( 197 , 198 ). The effects of gonadal hormones on NAc physiology is not limited to females, as long-term treatment with androgens in males also modulates NAc dendritic spine density ( 200 ).…”
Section: Reward Systemsmentioning
confidence: 99%
“…Investigating the interactions between sex, hormones, and environmental inputs such as stress or environmental chemical exposure is an essential future line of research. Regarding male MSNs, another possibility is that testosterone regulates excitatory synaptic input onto nucleus accumbens neurons, as suggested by experiments analyzing dendritic spine density in response to week-long exogenous testosterone exposure in gonad-intact male rats ( 107 ), and the role of androgens in reward-related behaviors ( 108 ).…”
Section: Excitatory Synapse Number Is Increased Onto Female Compared mentioning
confidence: 99%
“…Here we used an additional control group of intact males to also establish that gonadal hormones are not necessary to maintain spine density and morphology in the striatum in males, as GDX left these variables unaffected. Another group found that in intact males, a chronic high dose of testosterone decreases spine density in the NAcSh, and has no effect on the NAcC (Wallin-Miller et al, 2016). This suggests that androgens induce loss of spines in the NAcSh regardless of whether the male is gonadectomized or not.…”
Section: Discussionmentioning
confidence: 99%